The Effect of Beta-Cyclodextrin on the Iodometric Determination of Some Penicillins Reported in USP and BP: Iodometric determination of penicillins - Zahra Ramezani; Nadereh Rahbar; Mehdi Shadmani; Yousef Ekhteraee Toosi (Iranian Journal of Pharmaceutical Sciences, 2012)
This work summarizes how the efficiency of pharmacopeias (USP and BP) procedures for the iodometric determination of pencillins can be significantly enhanced through the use of beta-cyclodextrin (β-CD). In the commonly used iodometric method, titration takes about 30 min; 15 min to hydrolyze the antibiotics and 15 min for reaction between iodine and hydrolyzed species. The experimental results indicate that β-CD accelerates both hydrolysis of amoxicillin, ampicilline and cloxacilline and the reaction of their hydrolyzed products with iodine. Effect of different parameters such as sodium hydroxide, hydrochloric acid concentrations, and the waiting times in the presence of β-CD on the total titration times reported in pharmacopeia are evaluated. Finally, it is shown that the analysis times of iodometric assay for ampiciline an d amoxicilin in the presence of 0.108 mg.ml-1 β-CD are reduced from 30 to 5 min and those of cloxaciline is reduce to 10 min. The iodometric titration in the presence of β-CD is referred to as modified USP. Student t-tests at 95% level shows that there are no significant differences between USP and Modified USP. It is also shown that β-CD increases the stability of penicillin-G relative to USP buffer No.1. The reliability of the proposed method is evaluated by analysis of the above mentioned antibiotics in different pharmaceutical forms. The results show that the modified method can be successfully applied for the assay of cloxaciline injection vial, amoxicillin and ampicillin capsules and suspensions.